Potent inhibition of drug-resistant HIV protease variants by monoclonal antibodies - Bartonová, Vanda; Král, Vlastimil; Sieglová, Irena; Brynda, Jirí; Fábry, Milan; Horejsí, Magdalena; Kozísek, Milan; Sasková, Klára Grantz; Konvalinka, Jan; Sedlácek, Juraj; Rezácová, Pavlína (Antiviral research, 2008)
The monoclonal antibodies 1696 and F11.2.32 strongly inhibit the activity of wild-type HIV-1 protease (PR) by binding to epitopes at the enzyme N-terminus (residues 1-6) and flap residues 36-46, respectively. Here we demonstrate that these antibodies are also potent inhibitors of PR variants resistant to active-site inhibitors used as anti-AIDS drugs. Our in vitro experiments revealed that the inhibitory potency of single-chain fragments (scFv) of these antibodies is not significantly affected by the presence of mutations in PR; inhibition constants for drug-resistant protease variants are 5-11 nM and 13-169 nM for scFv1696 and for scFvF11.2.32, respectively. Tethered dimer of HIV-1 PR variant proved to be a model protease variant resistant to dissociative inhibition by 1696, and, strikingly, it also displayed resistance to inhibition by F11.2.32 suggesting that dimer dissociation also plays a role in the inhibitory action of F11.2.32.
Keywords: Immunoglobulin Fragments; Models, Molecular; Humans; Antiretroviral Therapy, Highly Active; HIV-proteasa; HIV Protease Inhibitors; HIV infekce; dimerizace; HIV Infections; Antibodies, Monoclonal; mutace; Dimerization; lidé; Recombinant Proteins; HIV Protease; imunoglobuliny - fragmenty; molekulární modely; genetická variace; virová léková rezistence; Genetic Variation; rekombinantní proteiny; Drug Resistance, Viral; vysoce aktivní antiretrovirová terapie; monoklonální protilátky; inhibitory HIV-proteasy; Mutation; HIV-1